Analisis Resiko Longsor Di Desa Garapia Menggunakan Electrical Resistivity Tomography (ERT) Untuk Identifikasi Kedalaman Bidang Gelincir - Katili, Gita Triyana Risti; Arifin, Yayu Indriati; Zainuri, Ahmad (Universitas Negeri Gorontalo, 2024)
This study explores the geological conditions and the depth of landslide slip surfaces in Garapia Village, North Gorontalo Regency, using Electrical Resistivity Tomography (ERT). By analyzing stratigraphy and geoelectrical data, the research aims to provide a comprehensive understanding of subsurface structures and their implications for landslide risks. Stratigraphic analysis reveals two primary geological units: weathered basalt, characterized by its grayish-black color, and alluvial deposits, indicating ongoing sedimentation. Structural analysis shows a Northeast-Southwest alignment, reflecting tectonic influences that may impact slope stability. ERT measurements identify three subsurface layers with varying resistivities: soil (10.6 – 783 Ωm), basalt (783 – 41,867 Ωm), and andesite (41,867 – 244,307 Ωm). A significant slip surface detected at depths of 9.85 to 18.7 meters shows low resistivity (4.75 – 48.1 Ωm), suggesting clay that is prone to landslides. The study highlights ERT's effectiveness in accurately identifying slip surface depths, offering valuable insights for landslide risk assessment and mitigation. This approach provides enhanced precision compared to traditional methods, thus improving disaster planning and risk management.